C90. Successful Procedure of Ductus Arteriosus Stenting: Promising Choice for Pulmonary Atresia Survival. (23rd November 2021) - Andini, R; Permitasari, D A; Priyatno, A
Abstract: Background: Duct-dependant circulation in a baby presents as a life threatening emergency. Maintain the duct patency is crucial for patient survival before they have an cardiac surgery. We describe a case of a baby with pulmonary atresia who underwent succesful procedure of patent ductus arteriosus (PDA) stenting. Case Summary: a female baby was born in peripheral hospital with birth weight of 3 kg by normal delivery, noticed to have cyanosis sixteen hours after birth. At our centre, the baby look cyanosed. Saturation by pulse oximetry was 84%. In physical examination appears, a continuous murmur was heard below clavicle at linea parasternal. Echocardiography confirmed the diagnosis of pulmonary atresia. Faint flow of PDA observed with duct size less than 1 mm. Prostaglandin E1 Infusion was start immediately at the rate of 1 µg/Kg/min. Within 6 hours of infusion the baby had an episode of apnoea. The baby then taken up for ductal stenting to keep the duct patent for few months before staged cardiac surgery. Discussion: Pulmonary atresia is an critical case of congenital heart disease. The systemic or pulmonary circulation are mantained through flow in patent ductus arteriosus. Before cardiac surgical repair these patient can survive only if duct patency is reliably maintained. PDA stenting has been shown to be as an acceptable and less invasive approach to maintain ductal patency.